La custodia compartida un paliativo al síndrome de alienación parental. - Espinosa Encarnacion, Marbelle Sofia; Pucha Pelaez, Byron Gustavo (Machala, 2021)
Shared custody allows the minor's relationship with both parents to be maintained; however, in practice and in the delivery of justice when determining custody, flaws are evident that cause emotional and affective disorders such as parental alienation syndrome. In order to establish some relevant considerations related to the custody of the children, a descriptive investigation of the bibliographic review type was carried out. The methodological strategy applied was systematized by historical-logical, exegetic, content analysis and synthetic-analytical methods. Among the most relevant findings is the legal vacuum existing in the Ecuadorian legislative system regarding the figure of shared custody, which leads to the violation of the principle of the best interests of the child and contributes to the appearance in the minor of the parental alienation syndrome.
La custodia compartida permite mantener la relación del menor con ambos progenitores; sin embargo, en la práctica y en la impartición de justicia a la hora de determinar la custodia se evidencian falencias que provocan trastornos emocionales y afectivos como el síndrome de alienación parental. Con el objetivo de establecer algunas consideraciones relevantes que guardan relación a la custodia de los hijos(as), se realizó una investigación descriptiva de tipo revisión bibliográfica. La estrategia metodológica aplicada se sistematizó mediante los métodos histórico-lógico, exegético, análisis de contenido y analítico sintético. Entre los hallazgos más relevantes se encuentra el vacío legal existente en el ordenamiento legislativo ecuatoriano respecto a la figura de la custodia compartida, lo que acarrea la vulneración del principio del interés superior del menor y contribuye a la aparición en el menor del síndrome de alienación parental.
Keywords: CUSTODIA COMPARTIDA; SINDROME DE ALIENACION PARENTAL; INTERES SUPERIOR DEL MENOR